a AN ANALYSIS METAPHOR IN DAUGHTRY’S MUSIC ALBUM : metaphor - wopari, edwart (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2024)
Abstract— Language is the primary media to communicate, This study concerns analyzing metaphors from American rock band Daughtry, released on November 21, 2006, by RCA Records. The band was fronted by American Idol season five finalist Chris Daughtry. The release is the fastest-selling rock debut album in Soundscan history and the band's best-selling record. There are two problems that are formulated in this study, are: (1) To know the types of metaphorical expression from Daughtry. (2) To convey the meaning of metaphors from Daughtry, there are two theories used in this research the first theory proposed by George Lakoff and Mark Johnson (1980) that is used to identify metaphora and the second theory is the theory of meaning which supported by Leech (1981) to analyze the meaning. The research employs a semantics approach to the song lyrics, which contain metaphors by Lakoff and Johnson in multiple stanzas and also explained the significance of the metaphors Daughtry's used in their lyrics. The method of this research is using qualitative analysis. The research questions will be answered in an analytical description. The result of this research shows that all types of metaphors are found in the data, with the ontological metaphor as the most frequently used type of metaphor based on Lakoff and Johnson's theory.